Mountain pastoralism and spatial mobility in the South-Peruvian andes in the age of state formation (1880-1969 and beyond) - Sendón, Pablo Federico (2009)
The process of inclusion of the colonial 'Republic of Indians' into the framework of the Peruvian state involved a series of changes in the Indian's judicial status. This article examines the legal metamorphosis experienced by a shepherd population in Southern Peru, Phinaya, on the basis of both historical and ethnographical information. The aim of the article is to examine the extent to which republican policies designed during the nineteenth and twentieth centuries recognized the existence of shepherd populations in the territory of the nation. It also explores to what extent, if any, the twentieth century policies designed to incorporate these populations within a national territory newly defined by its boundaries took account of their patterns of social organization in relation to one aspect of south Peruvian pastoralism: spatial mobility.